Stress in ASME pressure vessels, boiler and nuclear components - Jawad, Maan H. (Engineering professional collection, 2018)
Written for professional mechanical engineers and students, this text offers a resource to the theories and applications that are needed to achieve an understanding of stress loads and design of plates and shell components in compliance with pressure vessel, boiler, and nuclear standards. --